Cardiovascular morbidity and mortality in psoriasis and psoriatic arthritis: a systematic literature review. (11th July 2013) - Horreau, C.; Pouplard, C.; Brenaut, E.; Barnetche, T.; Misery, L.; Cribier, B.; Jullien, D.; Aractingi, S.; Aubin, F.; Joly, P.; Le Maître, M.; Ortonne, J.‐P.; et al.
Abstract: Previous epidemiological studies have demonstrated a high prevalence of cardiovascular (CV) risk factors in psoriasis patients, including metabolic syndrome, cigarette smoking, obesity, hypertension, diabetes mellitus, insulin resistance and dyslipidaemia. An increase in CV morbidity and mortality attributable to psoriasis is still under question. Primary objective: to assess CV morbidity and mortality in psoriasis and psoriatic arthritis (PsA) including stroke, coronary artery disease, myocardial infarction (MI) and peripheral artery disease. Secondary objectives: to assess if psoriasis per se is an independent CV risk factor and if psoriasis severity is a predictor of CV risk. We also evaluated the effect of conventional systemic treatments for psoriasis on CV mortality. A systematic literature search was carried out from 1980 to December 2011, in the Embase, Medline and Cochrane Library databases, in English and French using a combination of keywords including (Psoriasis) OR (Psoriatic arthritis) AND (Myocardial infarction) OR (Coronaropathy) OR (Stroke) OR (Cardiovascular) AND (Methotrexate) AND (Ciclosporin) AND (Retinoids). Of the 929 identified references, 33 observational studies evaluating the rates of cardiovascular events (CVE) in patients with psoriasis and PsA compared with controls were selected. Meta‐analysis of both cohort and cross‐sectional studies showed an increased risk of MI with Odds Ratio (OR) of 1.25 (95% CI 1.03–1.52) and 1.57 (95% CI 1.08–2.27) in psoriasis and PsA, respectively, compared with the general population. The risk of MI was more pronounced for patients having severe psoriasis and for patients with psoriasis of early onset. It remained significantly elevated after controlling for major CV risk factors. The meta‐analysis identified a small, but significant association between psoriasis, PsA and coronary artery disease with an OR between 1.19 (95% CI 1.14–1.24) for cross‐sectional studies, 1.20 (95% CI 1.13–1.27) for cohort studies and 1.84 (95% CI 1.09–3.09) for case–control studies. The risk of coronary artery disease seemed to be more pronounced in patients with severe psoriasis and in patients with psoriasis of early onset. The meta‐analysis assessing the risk of stroke gave inconclusive results: analysis of cross‐sectional studies suggested that psoriasis patients had a slightly higher risk of stroke with an OR of 1.14 (95% CI 1.08–1.99), whereas the meta‐analysis of cohort studies failed to show an association. There was also an increased risk of peripheral artery disease in psoriasis. No significant increased risk of CV mortality could be shown for both psoriasis and PsA patients. The use of methotrexate was associated with a reduced incidence of cardiovascular disease in two studies. The use of etretinate was associated with a reduction of CV mortality in one study. Potential selection bias such as the 'healthy user effect' prevents from drawing definite conclusions. There may be a small, but significant increased risk of CVE, but not of CV mortality in psoriasis and PsA patients. The psoriasis attributable risk remains difficult to assess due to confounding factors. The moderate quality of CV risk factors reporting in studies should be acknowledged. In addition, heterogeneity in study design, outcome definition and assessment represent major limitations. Nevertheless, screening and management of CV risk factors are important in psoriasis.